Methods and forms of state regulation of the economy ("Journal "U". Economy. Management. Finance.", 2023)
This article discusses various methods of state regulation of the economy, which are used to meet public needs and restore balance in the economic market. Such methods are monetary and fiscal policy, as well as other methods, such as regulating prices and imports of products, developing competition, setting standards for product safety and quality, etc. The article discusses specific examples of economic regulation in Japan and the United States. At the end of the article, the author concludes that there is a need for competent use of state regulation of the economy in combination with an economic incentive and a free market to achieve stable economic development.
Keywords: methods; forms; government regulation; economics; fiscal policy; monetary policy; tariff policy; trade policy; structural policy; social policy; innovation policy; regional policy; legislation; budget; central bank; government; tax service; control and audit bodies; monitoring organizations